PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, DAN KEBIJAKAN DIVIDEN TERHADAP KOEFISIEN RESPON LABA - Nana Novianti (Faculty of Economic and Business, 2014)
The aim of this research is to empirically examine the influence of the capital structure, firm size and dividend policy of the earnings response coefficients and the influence of conservatism accounting as moderation variable. Techniques of data analysis in this study used moderated regression Analysis. The results of this study showed that partially results of the study showed that capital structure and firm size had negatif and significant effect on earnings response coefficients, but the dividend policy had not significant effect on earnings response coefficients. Capital structure had does not affect accounting conservatism moderated the earnings response coefficient; firm size moderated accounting conservatism and dividend policy had an affect on moderated accounting conservatism effect on earnings response coefficientsDOI: 10.15408/etk.v13i2.1882